Time-to-smile, time-to-speak, time-to-resolve: timescales for shaping engagement in language. (September 2022) - Rączaszek-Leonardi, Joanna; Główka, Krzysztof; Nomikou, Iris; Rossmanith, Nicole
Abstract: This paper is a further step toward the construction of an ecologically valid framework for the emergence of symbolic communication in development. Building on recent advancements, which view language learning in terms of the increasingly skillful usage and navigation of interactive affordances within a re-enacted social world, we present a more detailed investigation of the timing of such affordances and the role of that timing in the progressive structuring of communication toward symbolic language. Seeking conceptual similarities with an action-based ecological framework, we extend the concepts of that framework to the context of early social interaction. We abandon a conception of language learning by infants as based on sound-reference mappings and envision this process as an attunement to structures in time, which entails the infant becoming increasingly able to engage in those structures, that is, to navigate and shape the relevant interactive dynamics skillfully. We illustrate attunements to several timing orders that are essential to the emergence of language: i) to participants' actions within routines, which leads to the emergence of social affordances; ii) to partners' vocalizations within an individuated layer, which supports perception of the systemic properties of language; and iii) to larger structures in time, shaped by energetic and affective envelopes, which facilitates discerning important semantic units. The goal of this work is to show how embodied interactions gain their linguistic character for the infant and how the structure of interactive engagements becomes increasingly complex and language-dependent without ever becoming fully ungrounded from interaction. Highlighting the importance of timing for learning to participate should improve our understanding of the progressive saturation of language with interactive structures for a child on the one hand and our understanding of the structuring of language as an interactive control on different timescales on the other.